Breeding durum wheat for grain yield and quality - Josephides C.M. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
In Cyprus the practised breeding method, which is a modification of the pedigree method, retains for subsequent exploration F3 lines with a higher frequency of potential genes for high quality. Thereafter, two site replicated yield testing of the F4 bulk lines at two sites increases the chances of selecting individuals in this generation, which combine acceptable grain and processing quality along with higher frequency of desirable genes for grain yield. Five spikes selected from each of the F4 bulk lines with higher average yield, are retained for subsequent exploration in the F5. Outstanding lines enter the preliminary yield trials. The referred methodology resulted in the development of the high yielding and quality durum wheat cultivar 'Macedonia' which is grown in most of the durum wheat areas.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)